ChemInform Abstract: Highly Efficient Dehydrogenative Coupling of Hydrosilanes with Amines or Amides Using Supported Gold Nanoparticles. Issue 27 (18th June 2015) - Mitsudome, Takato; Urayama, Teppei; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract Hydroxyapatite‐supported gold nanoparticles with a mean diameter of 3.0 nm are found to be optimal for the preparation of monoaminesilanes or ‐silylamides using equimolar ratio of reactants.